Tin-based perovskite material, thin film and preparation method and application thereof

By using hexafluorophosphate additives in tin-based perovskite materials to synergize with the tin source, the oxidation of Sn2+ and the crystallization kinetics are suppressed, and the problem of Sn2+ is easily oxidized in tin-based perovskite materials is solved, and the stability and photoelectric properties of the material are significantly improved.

CN119730681APending Publication Date: 2025-03-28NANHUA UNIV

Patent Information

Application Number
CN202411861490.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Sn2+ in existing tin-based perovskite materials is easily oxidized, resulting in unstable material lattice and affecting the crystal quality and photoelectric properties of the film.

Method used

By synergistically acting with a tin source (such as perovskite precursor), the oxidation of Sn2+ is inhibited, and the crystallization kinetics of tin-based perovskite materials are regulated, thereby improving the crystallization quality of the film.

Benefits of technology

It effectively improves the stability and photoelectric properties of tin-based perovskite materials, and solves the problems of difficulty in film formation, low efficiency and poor stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730681A_ABST
    Figure CN119730681A_ABST
Patent Text Reader

Abstract

The invention discloses a tin-based perovskite material, a thin film and a preparation method and application thereof, and belongs to the technical field of perovskite materials, a hexafluorophosphate additive is adopted, and the additive and a tin-containing raw material (especially a perovskite precursor) have a synergistic effect, so that the defects of the tin-based perovskite material can be improved. The hexafluorophosphate additive has reducibility and can interact with Sn < 2 + > in the tin-based perovskite, oxidation of Sn < 2 + > in the tin-based perovskite is effectively inhibited, meanwhile, the crystallization kinetics of growth of the tin-based perovskite material can be regulated and controlled, the crystallization quality of the tin-based perovskite thin film is improved, and the performance of the tin-based perovskite thin film is improved. The defects that a tin-based perovskite thin film is difficult to form, the efficiency is low, and the stability of tin-based perovskite is poor are overcome, and then the stability and the photoelectric property of the tin-based perovskite material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite materials, and in particular to a tin-based perovskite material, a film, and a preparation method and application thereof. Background Art

[0002] Compared with traditional crystalline silicon and inorganic thin-film solar cells, perovskite solar cells have been widely studied due to their simple preparation process and low cost. Currently, high-performance perovskite cells are usually developed based on lead-based perovskite materials. The presence of Pb will cause serious pollution to the environment and is not conducive to the industrialization of perovskite cells. Tin-based perovskite cells overcome this defect. Compared with lead-based perovskite materials, tin-based perovskite materials have higher charge mobility and higher theoretical limit efficiency.

[0003] However, the Sn in existing tin-based perovskite materials 2+ Tin-based perovskite materials are easily oxidized, and the lattice instability leads to poor film crystallization quality. Therefore, the photoelectric performance of cells prepared using conventional tin-based perovskite materials cannot meet people's demand for perovskite solar cells. Summary of the invention

[0004] The present invention provides a tin-based perovskite material, a film, a preparation method and an application thereof, and utilizes the synergistic effect of hexafluorophosphate and a tin source (especially a perovskite precursor) to effectively improve the defects of the tin-based perovskite material. 2+ interaction, effectively inhibiting the Sn 2+ At the same time, it can regulate the crystallization kinetics of the growth of tin-based perovskite materials, improve the crystallization quality of tin-based perovskite films, improve the defects of difficult film formation, low efficiency and poor stability of tin-based perovskite films, and thus improve the stability and photoelectric properties of tin-based perovskite materials.

[0005] The first object of the present invention is to provide a tin-based perovskite material, characterized in that it is composed of hexafluorophosphate and a tin source in a molar ratio of 0.1 to 1.5:100.

[0006] As a preferred embodiment, the tin source includes a perovskite precursor solution or stannous halide.

[0007] As a preferred embodiment, the chemical formula of the perovskite precursor is AB1Y1Y2Y3 or AB1B2Y1Y2Y3, wherein A is a formamidinium cation or a methylamine cation, B1 is a tin ion, B2 is a lead ion, and Y1, Y2, and Y3 are each independently a halogen ion.

[0008] As a preferred embodiment, the hexafluorophosphate includes at least one of 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate, tetramethylchloroformamidine hexafluorophosphate, benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate or bromotris(dimethylamino)phosphonium hexafluorophosphate.

[0009] The second object of the present invention is to provide a tin-based perovskite film prepared from the above-mentioned tin-based perovskite material.

[0010] The third object of the present invention is to provide a method for preparing a tin-based perovskite film, comprising the following steps:

[0011] A tin source and hexafluorophosphate are mixed at a molar ratio of 100:0.1-1.5 to obtain a mixture, the mixture is spin-coated on a substrate surface, and an anti-solvent is added to obtain a wet film; the wet film is annealed at 50-250° C. to obtain a tin-based perovskite film.

[0012] As a preferred implementation manner, the annealing treatment time is 5 to 90 minutes.

[0013] As a preferred implementation, the tin-based perovskite film has a thickness of 0.05 to 10 μm and a roughness of less than 50 nm.

[0014] A fourth object of the present invention is to provide an application of a tin-based perovskite film in the preparation of a perovskite solar cell.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention provides a tin-based perovskite material, a film, a preparation method and an application thereof, wherein a hexafluorophosphate additive is used, and the additive and the tin-containing raw material (especially the perovskite precursor) synergistically act to improve the defects of the tin-based perovskite material. The hexafluorophosphate additive has a reducing property and can react with the Sn of the tin-based perovskite to reduce the defects of the tin-based perovskite. 2+ interaction, effectively inhibiting the Sn 2+ At the same time, it can regulate the crystallization kinetics of the growth of tin-based perovskite materials, improve the crystallization quality of tin-based perovskite films, improve the defects of difficult film formation, low efficiency and poor stability of tin-based perovskite films, and thus improve the stability and photoelectric properties of tin-based perovskite materials.

[0017] The tin-based perovskite material of the present invention is applied to perovskite solar cells, and the photoelectric performance of the perovskite solar cells is significantly improved. The tin-based perovskite material of the present invention is applied to the preparation of electronic devices, which can improve the stability of the electronic devices. The tin-based perovskite material of the present invention has the prospect of being applied to other optoelectronic information functional materials, such as photodetectors, LED light-emitting devices and field effect transistors. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic diagram of the structure of a tin-based perovskite solar cell in Example 1 of the present invention;

[0019] Figure 2 A schematic diagram of the structural components of a tin-based perovskite solar cell in Example 1 of the present invention;

[0020] Figure 3 This is a scanning electron microscope test result diagram of the tin-based perovskite film in Comparative Example 1 of the present invention;

[0021] Figure 4 This is a scanning electron microscope test result diagram of the tin-based perovskite film in Example 1 of the present invention;

[0022] Figure 5 is a particle size distribution diagram of the crystal grains contained in the tin-based perovskite film in Comparative Example 1 of the present invention;

[0023] Figure 6 This is a particle size distribution diagram of the crystal grains contained in the tin-based perovskite film in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.

[0025] In view of the technical problem mentioned in the background technology that as people's requirements for the performance of perovskite solar cells continue to increase, the photoelectric performance of cells prepared using conventional tin-based perovskite materials is increasingly difficult to meet people's needs, the present invention proposes a tin-based perovskite material, a film, and a preparation method and application thereof, which utilizes the synergistic effect of hexafluorophosphates and tin sources (especially perovskite precursors) to effectively improve the defects of tin-based perovskite materials. 2+ interaction, effectively inhibiting the Sn 2+At the same time, it can regulate the crystallization kinetics of the growth of tin-based perovskite materials, improve the crystallization quality of tin-based perovskite films, improve the defects of difficult film formation, low efficiency and poor stability of tin-based perovskite films, and thus improve the stability and photoelectric properties of tin-based perovskite materials.

[0026] The technical solution of the present invention is described in detail below.

[0027] The present invention firstly provides a tin-based perovskite material, which is composed of hexafluorophosphate and a tin source in a molar ratio of 0.1 to 1.5:100.

[0028] In the above technical solution, compared with the Sn in the traditional tin-based perovskite material 2+ The present invention adopts an ionic liquid additive, a hexafluorophosphate additive, which synergizes with the tin-containing raw material (especially the perovskite precursor) to improve the defects of the tin-based perovskite material: the addition of the hexafluorophosphate additive can inhibit the Sn in the tin-based perovskite. 2+ Oxidation of Sn 2+ The defects caused by oxidation and the anti-site defects of Sn-I can improve the crystallization quality of tin-based perovskite materials and the quality of tin-based perovskite materials is high.

[0029] The additive in the present invention is of ionic type, and its ionic configuration has better flexibility in regulating tin-based perovskite, can accurately passivate the internal defects of tin-based perovskite film, and can participate in the formation of tin-based perovskite lattice, which is helpful for stabilizing the tin-based perovskite lattice.

[0030] The tin source used in the present invention includes a perovskite precursor solution or stannous halide. The chemical formula of the perovskite precursor is AB1Y1Y2Y3 or AB1B2Y1Y2Y3, wherein A is a carboxamidinium cation or a methylamine cation, B1 is a tin ion, B2 is a lead ion, and Y1, Y2, and Y3 are independently halogen ions.

[0031] Through the above implementation, the obtained perovskite material has excellent photoelectric conversion efficiency and low production cost. The perovskite precursor component (ABY1Y2Y3 or AB1B2Y1Y2Y3) and the hexafluorophosphate additive synergistically act to further improve the MA or FA vacancy defects, Sn in the tin-based perovskite film. 2+ The defects caused by oxidation and the effect of Sn-I anti-site defects improve the stability and photoelectric properties of tin-based perovskite films.

[0032] The stannous halide material includes stannous iodide and stannous fluoride, and the preparation raw materials also include formamidine amine halide.

[0033] The perovskite precursor solution is obtained by mixing stannous halide, formamidine amine halide, and a precursor solvent, specifically, by mixing formamidine amine iodide, stannous iodide, stannous fluoride, and a precursor solvent to obtain the perovskite precursor solution. The molar ratio of formamidine amine iodide, stannous iodide, and stannous fluoride is (0.8-1.2):(0.8-1.2):(0.02-0.2).

[0034] The precursor solvent includes at least one of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N-methylpyrrolidone or γ-butyrolactone.

[0035] In some preferred embodiments of the present invention, the precursor solvent includes DMF and DMSO, and the volume ratio of DMF to DMSO is (2-6):1.

[0036] In some more preferred embodiments of the present invention, in the perovskite precursor solution, the concentration of the perovskite precursor component is 0.1 to 3 mol / L.

[0037] In some more preferred embodiments of the present invention, in the perovskite precursor solution, the concentration of the perovskite precursor component is 0.6 to 1.6 mol / L.

[0038] The hexafluorophosphate used in the present invention is at least one of 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate, tetramethylchloroformamidine hexafluorophosphate, benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate or bromotris(dimethylamino)phosphonium hexafluorophosphate.

[0039] It should be noted that the hexafluorophosphate used in the present invention has reducing properties and can react with the Sn of the tin-based perovskite. 2+ interaction, which can effectively inhibit the Sn 2+ The oxidation of tin-based perovskite can also be regulated, and the crystallization kinetics of the growth of tin-based perovskite materials can be adjusted to improve the defects of difficult film formation, low efficiency and poor stability of tin-based perovskite films, thereby improving the stability and photoelectric properties of perovskite films. Specifically, for example, 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate, the Br and hexafluorophosphate groups in its molecules can react with Sn in the perovskite. 2+ Strong interactions occur, and the molecules are also reductive, which can effectively inhibit the Sn in perovskite 2+ oxidation, improving the structure and photoelectric properties of tin-based perovskites.

[0040] Therefore, under the synergistic effect of hexafluorophosphate and tin-containing raw materials (such as perovskite precursor solution), the defects of tin-based perovskite films can be improved and the Sn 2+ of oxidation.

[0041] The present invention also provides a tin-based perovskite film, which is prepared from the above-mentioned tin-based perovskite material. The preparation method of the tin-based perovskite film comprises the following steps:

[0042] The tin source and hexafluorophosphate are mixed to obtain a mixture, and an anti-solvent is used for spin coating to obtain a wet film; the wet film is annealed at 50-250° C. for 5-90 minutes to obtain a tin-based perovskite film with a thickness of 0.05-10 μm and a roughness of less than 50 nm.

[0043] A mixture of a hexafluorophosphate additive (such as 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate) and a tin-based perovskite precursor solution is treated with an anti-solvent to form a wet film, so as to form a tin-based perovskite film. The wet film is annealed to form a tin-based perovskite film, wherein the hexafluorophosphate additive (such as 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate) has a reducing property and can react with the Sn of the tin-based perovskite. 2+ interaction, which can effectively inhibit the Sn 2+ At the same time, it can regulate the crystallization kinetics of the growth of tin-based perovskite films, improve the defects of difficult film formation, low efficiency and poor stability of tin-based perovskite films, and thus improve the stability and photoelectric properties of tin-based perovskite films.

[0044] The fourth object of the present invention is to provide an application of a tin-based perovskite film in the preparation of a perovskite solar cell, wherein the perovskite solar cell comprises a conductive substrate, a hole transport layer, a perovskite light absorbing layer, an electron transport layer and an electrode stacked in sequence.

[0045] The perovskite light-absorbing layer used is the tin-based perovskite film prepared by the present invention, and the addition of the hexafluorophosphate additive can significantly improve the quality of the perovskite light-absorbing layer, and the perovskite light-absorbing layer has good stability and excellent photoelectric performance. The perovskite light-absorbing layer is applied to the perovskite solar cell, which can improve the photoelectric performance and service life of the solar cell.

[0046] In some embodiments of the present invention, the thickness of the perovskite light absorbing layer is 0.05 to 10 μm.

[0047] In some preferred embodiments of the present invention, the thickness of the perovskite light absorbing layer is 0.2-1 μm.

[0048] In some more preferred embodiments of the present invention, the hole transport layer is composed of poly(3,4-ethylenedioxythiophene) (PEDOT) and poly(styrene sulfonate) (PSS), specifically: taking a PEDOT:PSS solution, coating, and annealing to obtain the hole transport layer.

[0049] In some more preferred embodiments of the present invention, the thickness of the hole transport layer is 0.01-0.5 μm.

[0050] In some more preferred embodiments of the present invention, the conductive substrate comprises a substrate and a conductive layer, and the conductive layer is located between the substrate and the hole transport layer.

[0051] In some more preferred embodiments of the present invention, the conductive substrate is a glass substrate with an indium tin oxide (ITO) layer deposited thereon.

[0052] In some more preferred embodiments of the present invention, the electron transport layer comprises a fullerene (C60) layer, the fullerene layer is formed of a material containing fullerene, the thickness of the fullerene layer is 10-100 nm, specifically, the electron transport layer is formed of a material containing fullerene at a vacuum degree of <10 -5 Pa by thermal evaporation to obtain the fullerene layer.

[0053] In some more preferred embodiments of the present invention, the electron transport layer further comprises an interface modification layer, and the fullerene layer is located between the interface modification layer and the perovskite light absorption layer.

[0054] In some more preferred embodiments of the present invention, the interface modification layer is formed of a material containing dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP), and the thickness of the interface modification layer is 1 to 20 nm. Specifically, when the vacuum degree is less than 10 -5 BCP is deposited by thermal evaporation under the condition of 1.5777 W / m2 Pa to obtain the interface modification layer.

[0055] The electrode is a metal electrode, including at least one of copper, gold or silver.

[0056] In some more preferred embodiments of the present invention, the metal electrode is formed of a material containing Cu and / or Ag.

[0057] In some more preferred embodiments of the present invention, the method for preparing the metal electrode comprises the following steps: -5 Pa by thermal evaporation deposition to obtain the metal electrode.

[0058] In some more preferred embodiments of the present invention, the thickness of the electrode is 40 to 200 nm.

[0059] In some more preferred embodiments of the present invention, the thickness of the electrode is 80 to 120 nm.

[0060] The method for preparing the above-mentioned perovskite solar cell of the present invention comprises the following steps:

[0061] S1, preparing a hole transport layer on the surface of a conductive substrate;

[0062] S2, preparing a perovskite light absorbing layer on the surface of the hole transport layer.

[0063] In some preferred embodiments of the present invention, in step S1, the conductive substrate is a glass substrate deposited with ITO, and before preparing the hole transport layer, the glass substrate deposited with ITO is pre-treated, specifically: the glass substrate deposited with ITO is subjected to continuous multi-step ultrasonic cleaning, including ultrasonic cleaning with a detergent, deionized water, acetone, and ethanol in sequence, and drying after ultrasonic cleaning.

[0064] In some more preferred embodiments of the present invention, the glass substrate deposited with ITO needs to be irradiated with ultraviolet light before use.

[0065] In some preferred embodiments of the present invention, in step S1, a PEDOT:PSS solution is taken, filtered, spin-coated on a conductive substrate, and annealed to obtain a hole transport layer, wherein the annealing temperature is 80-200° C., the annealing time is 5-60 min, the spin-coating speed is 2000-8000 rpm, and the spin-coating time is 10-120 s.

[0066] In some preferred embodiments of the present invention, the preparation method further comprises step S3, preparing an electron transport layer on the surface of the perovskite light absorbing layer, specifically: on the surface of the perovskite light absorbing layer, in a vacuum degree of <10 -5 The electron transport layer was prepared by depositing the fullerene layer and the BCP layer at one time by thermal evaporation under Pa conditions.

[0067] In some preferred embodiments of the present invention, the preparation method further comprises step S4, preparing an electrode on the surface of the electron transport layer, wherein the electrode is a metal electrode, and the preparation method of the metal electrode is specifically as follows: on the surface of the electron transport layer, in a vacuum degree of <10 -5 The metal electrode was prepared by thermal evaporation deposition under the condition of Pa.

[0068] The technical effects of the present invention are described below through specific embodiments.

[0069] Example 1

[0070] A tin-based perovskite material is composed of 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate and a FASnI3 perovskite precursor in a molar ratio of 0.8:100.

[0071] The above-mentioned tin-based perovskite material is used to prepare a tin-based perovskite film with a thickness of 0.3 μm, a grain size of 0.1 to 1 μm, and a roughness of less than 50 nm. The preparation process includes:

[0072] (1) Formamidinium iodide (FAI), stannous iodide (SnI2) and stannous fluoride (SnF2) were weighed in a glove box at a molar ratio of 1:1:0.1 and dissolved in a DMF / DMSO (DMF / DMSO volume ratio is 4:1) mixed solution to obtain a 1 mol / L concentration of FASnI3 perovskite precursor solution (referred to as precursor solution I).

[0073] (2) 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate is doped into precursor solution I to obtain a tin-based perovskite precursor solution containing 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate (referred to as precursor solution II), wherein in precursor solution II: based on the molar amount of precursor solution I being 100%, the added amount of 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate is 0.8%.

[0074] (3) Precursor solution II is dropped onto a substrate, and 150 μL of chlorobenzene is added as an anti-solvent under spin coating conditions of 3000-5000 revolutions for 30-60 seconds to form a thin wet film on the surface of the substrate. The substrate is a hole transport layer (PEDOT:PSS layer) formed by a PEDOT:PSS solution.

[0075] Wherein, the PEDOT:PSS solution is a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution purchased from Xi'an Biolight Optoelectronics Technology Co., Ltd., PEDOT:PSS (4083), J1104, with a concentration of 1.3% to 1.7% aqueous solution.

[0076] (4) The substrate and the thin wet film on the surface thereof are annealed at 80° C. for 10 min to obtain a stacked PEDOT:PSS layer and a tin-based perovskite film.

[0077] A perovskite solar cell is prepared by using the tin-based perovskite film prepared above, and its structural schematic diagram is shown as follows: Figure 1 The structural components are shown in Figure 2As shown, it includes a conductive substrate (a glass plate deposited with ITO, ITO is used as an anode), a hole transport layer (PEDOT:PSS), a perovskite light absorption layer (tin-based perovskite film), an electron transport layer (including a C60 layer and a BCP interface modification layer), and a cathode (metal electrode Ag) which are stacked in sequence.

[0078] The preparation process of the above-mentioned perovskite solar cell includes:

[0079] S1, treating a glass substrate deposited with ITO (referred to as ITO glass substrate), performing continuous multi-step ultrasonic cleaning on the glass substrate deposited with ITO, adding a detergent, deionized water, acetone, and ethanol in each ultrasonic cleaning tank in turn; drying the glass substrate deposited with ITO after ultrasonic cleaning; irradiating the cleaned glass substrate deposited with ITO with ultraviolet light, wherein the transmittance of the ITO glass substrate is 90%, the impedance is 7 ohms, and the model is 1.1mm 7 ohms; the cleaning agent is a glass cleaning agent purchased from Guangzhou Daily Chemical, and the specification is 12basic.

[0080] S2, preparation of PEDOT:PSS hole transport layer, the PEDOT:PSS solution was filtered, coated on a glass substrate deposited with ITO under spin coating conditions of 5000r / 30s, and then annealed on a hot plate at 140°C for 15min to obtain a PEDOT:PSS hole transport layer (thickness 50nm).

[0081] S3, preparation of perovskite light absorbing layer (tin-based perovskite film): using the PEDOT:PSS hole transport layer as the substrate, a tin-based perovskite film with a thickness of 0.3 μm is prepared on the surface of the PEDOT:PSS hole transport layer. The specific preparation steps are the same as steps (1)-(4) in this embodiment.

[0082] S4, preparation of electron transport layer: on the surface of perovskite light absorbing layer, in a vacuum degree <10 -5 The fullerene layer and the BCP interface modification layer were sequentially deposited by thermal evaporation under the condition of 40 nm and 8 nm in thickness, respectively.

[0083] S5, preparation of metal electrode: on the surface of BCP interface modification layer, under vacuum degree <10 -5 Ag is deposited by thermal evaporation under Pa conditions with a thickness of 100 nm (the thickness can be 80 to 120 nm).

[0084] The thickness of the tin-based perovskite film in this embodiment is 0.3 μm, which is a moderate thickness. The roughness of the tin-based perovskite film is less than 50 nm, and the flatness is relatively high.

[0085] Example 2

[0086] A tin-based perovskite material is composed of 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate and a FASnI3 perovskite precursor in a molar ratio of 0.8:100.

[0087] The above-mentioned tin-based perovskite material is used to prepare a tin-based perovskite film, wherein the thickness of the tin-based perovskite film is 0.3 μm and the roughness is less than 50 nm. The preparation process includes the following steps:

[0088] (1) Formamidinium iodide (FAI), stannous iodide (SnI2) and stannous fluoride (SnF2) were weighed in a glove box at a molar ratio of 1:1:0.1 and dissolved in a DMF / DMSO (DMF / DMSO volume ratio is 4:1) mixed solution to obtain a 1 mol / L concentration of FASnI3 perovskite precursor solution (referred to as precursor solution I).

[0089] (2) 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate is doped into precursor solution I to obtain a tin-based perovskite precursor solution containing 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate (referred to as precursor solution II), wherein in precursor solution II: based on the molar amount of precursor solution I being 100%, the added amount of 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate is 0.8%.

[0090] (3) Precursor solution II is dropped onto a substrate, and 150 μL of chlorobenzene is added as an anti-solvent under spin coating conditions of 3000-5000 revolutions for 30-60 seconds to form a thin wet film on the surface of the substrate. The substrate is a hole transport layer (PEDOT:PSS layer) formed by a PEDOT:PSS solution.

[0091] (4) The substrate and the thin wet film on the surface thereof are annealed at 80° C. for 10 min to obtain a stacked PEDOT:PSS layer and a tin-based perovskite film.

[0092] A perovskite solar cell is prepared using the tin-based perovskite film prepared as above, comprising a conductive substrate (a glass plate deposited with ITO, ITO used as an anode), a hole transport layer (PEDOT:PSS), a perovskite light absorption layer (tin-based perovskite film), an electron transport layer (including a C60 layer and a BCP interface modification layer), and a cathode (metal electrode Cu) which are stacked in sequence.

[0093] The preparation process of the above-mentioned perovskite solar cell includes:

[0094] A perovskite solar cell, which differs from Example 1 only in that Cu is used in the cathode of the battery to replace Ag in Example 1.

[0095] S1, treating a glass substrate deposited with ITO (referred to as ITO glass substrate), performing continuous multi-step ultrasonic cleaning on the glass substrate deposited with ITO, adding a detergent, deionized water, acetone, and ethanol in each ultrasonic cleaning tank in turn; drying the glass substrate deposited with ITO after ultrasonic cleaning; irradiating the cleaned glass substrate deposited with ITO with ultraviolet light, wherein the transmittance of the ITO glass substrate is 90%, the impedance is 7 ohms, and the model is 1.1mm 7 ohms; the cleaning agent is a glass cleaning agent purchased from Guangzhou Daily Chemical, and the specification is 12basic.

[0096] S2, preparation of PEDOT:PSS hole transport layer, the PEDOT:PSS solution was filtered, coated on a glass substrate deposited with ITO under spin coating conditions of 5000r / 30s, and then annealed on a hot plate at 140°C for 15min to obtain a PEDOT:PSS hole transport layer (thickness 50nm).

[0097] S3, preparation of perovskite light absorbing layer (tin-based perovskite film): using the PEDOT:PSS hole transport layer as the substrate, a tin-based perovskite film with a thickness of 0.3 μm is prepared on the surface of the PEDOT:PSS hole transport layer. The specific preparation steps are the same as steps (1)-(4) in this embodiment.

[0098] S4, preparation of electron transport layer: on the surface of perovskite light absorbing layer, in a vacuum degree <10 -5 The fullerene layer and the BCP interface modification layer were sequentially deposited by thermal evaporation under the condition of 40 nm and 8 nm in thickness, respectively.

[0099] S5, preparation of metal electrode: on the surface of BCP interface modification layer, under vacuum degree <10 -5 Cu was deposited by thermal evaporation under Pa conditions with a thickness of 100 nm.

[0100] Example 3

[0101] The only difference between this embodiment and Example 1 is that the same amount of tetramethylchloroformamidine hexafluorophosphate is used in this embodiment to replace the 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate in Example 1.

[0102] A tin-based perovskite material is composed of tetramethylchloroformamidine hexafluorophosphate and a FASnI3 perovskite precursor in a molar ratio of 0.8:100.

[0103] The tin-based perovskite material is used to prepare a tin-based perovskite film with a thickness of 0.3 μm. The preparation process of the tin-based perovskite film includes the following steps:

[0104] (1) Formamidinium iodide (FAI), stannous iodide (SnI2) and stannous fluoride (SnF2) were weighed in a glove box at a molar ratio of 1:1:0.1 and dissolved in a DMF / DMSO (DMF / DMSO volume ratio is 4:1) mixed solution to obtain a 1 mol / L concentration of FASnI3 perovskite precursor solution (referred to as precursor solution I).

[0105] (2) Tetramethylchloroformamidine hexafluorophosphate is doped into precursor solution I to obtain a tin-based perovskite precursor solution containing tetramethylchloroformamidine hexafluorophosphate (referred to as precursor solution II), wherein in precursor solution II: based on the molar amount of precursor solution I being 100%, the added amount of tetramethylchloroformamidine hexafluorophosphate is 0.8%.

[0106] (3) Precursor solution II is dropped onto a substrate, and 150 μL of chlorobenzene is added as an anti-solvent under spin coating conditions of 3000-5000 revolutions for 30-60 seconds to form a thin wet film on the surface of the substrate. The substrate is a hole transport layer (PEDOT:PSS layer) formed by a PEDOT:PSS solution.

[0107] (4) The substrate and the thin wet film on the surface thereof are annealed at 80° C. for 10 min to obtain a stacked PEDOT:PSS layer and a tin-based perovskite film.

[0108] A perovskite solar cell is prepared using the tin-based perovskite film prepared as above, comprising a conductive substrate (a glass plate deposited with ITO, ITO used as an anode), a hole transport layer (PEDOT:PSS), a perovskite light absorbing layer (tin-based perovskite film), an electron transport layer (including a C60 layer and a BCP interface modification layer), and a cathode (metal electrode Ag) which are stacked in sequence.

[0109] The perovskite light-absorbing layer of the perovskite solar cell in this embodiment uses tetramethylchloroformamidine hexafluorophosphate in the same amount of substance to replace the 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate in Example 1. The preparation process of the perovskite solar cell includes:

[0110] S1, treating a glass substrate deposited with ITO (referred to as ITO glass substrate), performing continuous multi-step ultrasonic cleaning on the glass substrate deposited with ITO, adding a detergent, deionized water, acetone, and ethanol in each ultrasonic cleaning tank in turn; drying the glass substrate deposited with ITO after ultrasonic cleaning; irradiating the cleaned glass substrate deposited with ITO with ultraviolet light, wherein the transmittance of the ITO glass substrate is 90%, the impedance is 7 ohms, and the model is 1.1mm 7 ohms; the cleaning agent is a glass cleaning agent purchased from Guangzhou Daily Chemical, and the specification is 12basic.

[0111] S2, preparation of PEDOT:PSS hole transport layer: the PEDOT:PSS solution was filtered and coated on a glass substrate deposited with ITO under spin coating conditions of 5000r / 30s, and then annealed on a hot plate at 140°C for 15min to obtain a PEDOT:PSS hole transport layer (thickness 50nm).

[0112] S3, preparation of perovskite light absorbing layer (tin-based perovskite film): using the PEDOT:PSS hole transport layer as the substrate, a tin-based perovskite film with a thickness of 0.3 μm is prepared on the surface of the PEDOT:PSS hole transport layer. The specific preparation steps are the same as steps (1)-(4) in this embodiment.

[0113] S4, preparation of electron transport layer: on the surface of perovskite light absorbing layer, in a vacuum degree <10 -5 The fullerene layer and the BCP interface modification layer were sequentially deposited by thermal evaporation under the condition of 40 nm and 8 nm in thickness, respectively.

[0114] S5, preparation of metal electrode: on the surface of BCP interface modification layer, under vacuum degree <10 -5 Ag was deposited by thermal evaporation under Pa conditions with a thickness of 100 nm.

[0115] Example 4

[0116] A perovskite solar cell, which differs from Example 3 only in that: in the cathode of the battery of this embodiment, Cu is used to replace the Ag in Example 3.

[0117] The above-mentioned tin-based perovskite film preparation process includes the following steps:

[0118] (1) Formamidinium iodide (FAI), stannous iodide (SnI2) and stannous fluoride (SnF2) were weighed in a glove box at a molar ratio of 1:1:0.1 and dissolved in a DMF / DMSO (DMF / DMSO volume ratio is 4:1) mixed solution to obtain a 1 mol / L concentration of FASnI3 perovskite precursor solution (referred to as precursor solution I).

[0119] (2) Tetramethylchloroformamidine hexafluorophosphate is doped into precursor solution I to obtain a tin-based perovskite precursor solution containing tetramethylchloroformamidine hexafluorophosphate (referred to as precursor solution II), wherein in precursor solution II: based on the molar amount of precursor solution I being 100%, the added amount of tetramethylchloroformamidine hexafluorophosphate is 0.8%.

[0120] (3) Precursor solution II is dropped onto a substrate, and 150 μL of chlorobenzene is added as an anti-solvent under spin coating conditions of 3000-5000 revolutions for 30-60 seconds to form a thin wet film on the surface of the substrate. The substrate is a hole transport layer (PEDOT:PSS layer) formed by a PEDOT:PSS solution.

[0121] (4) The substrate and the thin wet film on the surface thereof are annealed at 80° C. for 10 min to obtain a stacked PEDOT:PSS layer and a tin-based perovskite film.

[0122] A perovskite solar cell is prepared using the tin-based perovskite film prepared as above, comprising a conductive substrate (a glass plate deposited with ITO, ITO used as an anode), a hole transport layer (PEDOT:PSS), a perovskite light absorption layer (tin-based perovskite film), an electron transport layer (including a C60 layer and a BCP interface modification layer), and a cathode (metal electrode Cu) which are stacked in sequence.

[0123] The preparation process of the above-mentioned perovskite solar cell includes:

[0124] S1, treating a glass substrate deposited with ITO (referred to as ITO glass substrate), performing continuous multi-step ultrasonic cleaning on the glass substrate deposited with ITO, adding a detergent, deionized water, acetone, and ethanol in each ultrasonic cleaning tank in turn; drying the glass substrate deposited with ITO after ultrasonic cleaning; irradiating the cleaned glass substrate deposited with ITO with ultraviolet light, wherein the transmittance of the ITO glass substrate is 90%, the impedance is 7 ohms, and the model is 1.1mm 7 ohms; the cleaning agent is a glass cleaning agent purchased from Guangzhou Daily Chemical, and the specification is 12basic.

[0125] S2, preparation of PEDOT:PSS hole transport layer: the PEDOT:PSS solution was filtered and coated on a glass substrate deposited with ITO under spin coating conditions of 5000r / 30s, and then annealed on a hot plate at 140°C for 15min to obtain a PEDOT:PSS hole transport layer (thickness 50nm).

[0126] S3, preparation of perovskite light absorbing layer (tin-based perovskite film): using the PEDOT:PSS hole transport layer as the substrate, a tin-based perovskite film with a thickness of 0.3 μm is prepared on the surface of the PEDOT:PSS hole transport layer. The specific preparation steps are the same as steps (1)-(4) in this embodiment.

[0127] S4, preparation of electron transport layer: on the surface of perovskite light absorbing layer, in a vacuum degree <10 -5 The fullerene layer and the BCP interface modification layer were sequentially deposited by thermal evaporation under the condition of 40 nm and 8 nm in thickness, respectively.

[0128] S5, preparation of metal electrode: on the surface of BCP interface modification layer, under vacuum degree <10 -5 Cu was deposited by thermal evaporation under Pa conditions with a thickness of 100 nm.

[0129] Example 5

[0130] The only difference from Example 1 is that the same amount of benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate is used in this example to replace the 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate in Example 1.

[0131] A tin-based perovskite material is composed of benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate and a FASnI3 perovskite precursor in a molar ratio of 0.8:100.

[0132] The tin-based perovskite material is used to prepare a tin-based perovskite film with a thickness of 0.3 μm. The preparation process of the tin-based perovskite film includes:

[0133] (1) Formamidinium iodide (FAI), stannous iodide (SnI2) and stannous fluoride (SnF2) were weighed in a glove box at a molar ratio of 1:1:0.1 and dissolved in a DMF / DMSO (DMF / DMSO volume ratio is 4:1) mixed solution to obtain a 1 mol / L concentration of FASnI3 perovskite precursor solution (referred to as precursor solution I).

[0134] (2) Benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate is doped into precursor solution I to obtain a tin-based perovskite precursor solution containing benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate (referred to as precursor solution II), wherein in precursor solution II: based on the molar amount of precursor solution I being 100%, the added amount of benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate is 0.8%.

[0135] (3) Precursor solution II is dropped onto a substrate, and 150 μL of chlorobenzene is added as an anti-solvent under spin coating conditions of 3000-5000 revolutions for 30-60 seconds to form a thin wet film on the surface of the substrate. The substrate is a hole transport layer (PEDOT:PSS layer) formed by a PEDOT:PSS solution.

[0136] (4) The substrate and the thin wet film on the surface thereof are annealed at 80° C. for 10 min to obtain a stacked PEDOT:PSS layer and a tin-based perovskite film.

[0137] A perovskite solar cell is prepared using the tin-based perovskite film prepared as above, comprising a conductive substrate (a glass plate deposited with ITO, ITO used as an anode), a hole transport layer (PEDOT:PSS), a perovskite light absorbing layer (tin-based perovskite film), an electron transport layer (including a C60 layer and a BCP interface modification layer), and a cathode (metal electrode Ag) which are stacked in sequence.

[0138] The perovskite light-absorbing layer of the perovskite solar cell in this embodiment uses benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate in the same amount of substance to replace the 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate in Example 1. The preparation process of the perovskite solar cell includes:

[0139] S1, treating a glass substrate deposited with ITO (referred to as ITO glass substrate), performing continuous multi-step ultrasonic cleaning on the glass substrate deposited with ITO, adding a detergent, deionized water, acetone, and ethanol in each ultrasonic cleaning tank in turn; drying the glass substrate deposited with ITO after ultrasonic cleaning; irradiating the cleaned glass substrate deposited with ITO with ultraviolet light, wherein the transmittance of the ITO glass substrate is 90%, the impedance is 7 ohms, and the model is 1.1mm 7 ohms; the cleaning agent is a glass cleaning agent purchased from Guangzhou Daily Chemical, and the specification is 12basic.

[0140] S2, preparation of PEDOT:PSS hole transport layer, the PEDOT:PSS solution was filtered, coated on a glass substrate deposited with ITO under spin coating conditions of 5000r / 30s, and then annealed on a hot plate at 140°C for 15min to obtain a PEDOT:PSS hole transport layer (thickness 50nm).

[0141] S3, preparation of perovskite light absorbing layer (tin-based perovskite film): using the PEDOT:PSS hole transport layer as the substrate, a tin-based perovskite film with a thickness of 0.3 μm is prepared on the surface of the PEDOT:PSS hole transport layer. The specific preparation steps are the same as steps (1)-(4) in this embodiment.

[0142] S4, preparation of electron transport layer: on the surface of perovskite light absorbing layer, in a vacuum degree <10 -5 The fullerene layer and the BCP interface modification layer were sequentially deposited by thermal evaporation under the condition of 40 nm and 8 nm in thickness, respectively.

[0143] S5, preparation of metal electrode: on the surface of BCP interface modification layer, under vacuum degree <10 -5 Ag was deposited by thermal evaporation under Pa conditions with a thickness of 100 nm.

[0144] Example 6

[0145] A tin-based perovskite material is composed of benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate and a FASnI3 perovskite precursor in a molar ratio of 0.8:100.

[0146] The above-mentioned tin-based perovskite material is used to prepare a tin-based perovskite film, which is the same as Example 5.

[0147] A perovskite solar cell, which differs from Example 5 only in that: in the cathode of the battery of this embodiment, Cu is used to replace the Ag in Example 5.

[0148] The perovskite solar cell comprises a conductive substrate (a glass plate deposited with ITO, ITO is used as an anode), a hole transport layer (PEDOT:PSS), a perovskite light absorption layer (tin-based perovskite film), an electron transport layer (including a C60 layer and a BCP interface modification layer), and a cathode (metal electrode Cu) which are stacked in sequence. The preparation process comprises the following steps:

[0149] S1, treating a glass substrate deposited with ITO (referred to as ITO glass substrate), performing continuous multi-step ultrasonic cleaning on the glass substrate deposited with ITO, adding a detergent, deionized water, acetone, and ethanol in each ultrasonic cleaning tank in turn; drying the glass substrate deposited with ITO after ultrasonic cleaning; irradiating the cleaned glass substrate deposited with ITO with ultraviolet light, wherein the transmittance of the ITO glass substrate is 90%, the impedance is 7 ohms, and the model is 1.1mm 7 ohms; the cleaning agent is a glass cleaning agent purchased from Guangzhou Daily Chemical, and the specification is 12basic.

[0150] S2, preparation of PEDOT:PSS hole transport layer: the PEDOT:PSS solution was filtered and coated on a glass substrate deposited with ITO under spin coating conditions of 5000r / 30s, and then annealed on a hot plate at 140°C for 15min to obtain a PEDOT:PSS hole transport layer (thickness 50nm).

[0151] S3, preparation of perovskite light absorbing layer (tin-based perovskite film): using PEDOT:PSS hole transport layer as substrate, a tin-based perovskite film with a thickness of 0.3 μm is prepared on the surface of the PEDOT:PSS hole transport layer. The specific preparation steps are the same as steps (1)-(4) in Example 5.

[0152] S4, preparation of electron transport layer: on the surface of perovskite light absorbing layer, in a vacuum degree <10 -5 The fullerene layer and the BCP interface modification layer were sequentially deposited by thermal evaporation under the condition of 40 nm and 8 nm in thickness, respectively.

[0153] S5, preparation of metal electrode: on the surface of BCP interface modification layer, under vacuum degree <10 -5 Cu was deposited by thermal evaporation under Pa conditions with a thickness of 100 nm.

[0154] Example 7

[0155] The only difference between this embodiment and Example 1 is that the same amount of brominated tris(dimethylamino)phosphonium hexafluorophosphate is used in this embodiment to replace the 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate in Example 1.

[0156] A tin-based perovskite material is composed of brominated tris(dimethylamino)phosphonium hexafluorophosphate and a FASnI3 perovskite precursor in a molar ratio of 0.8:100.

[0157] The tin-based perovskite material is used to prepare a tin-based perovskite film with a thickness of 0.3 μm. The preparation process of the tin-based perovskite film includes the following steps:

[0158] (1) Formamidinium iodide (FAI), stannous iodide (SnI2) and stannous fluoride (SnF2) were weighed in a glove box at a molar ratio of 1:1:0.1 and dissolved in a DMF / DMSO (DMF / DMSO volume ratio is 4:1) mixed solution to obtain a 1 mol / L concentration of FASnI3 perovskite precursor solution (referred to as precursor solution I).

[0159] (2) Bromotris(dimethylamino)phosphonium hexafluorophosphate is doped into precursor solution I to obtain a tin-based perovskite precursor solution containing bromotris(dimethylamino)phosphonium hexafluorophosphate (referred to as precursor solution II), wherein in precursor solution II: the molar amount of precursor solution I is 100%, and the addition amount of bromotris(dimethylamino)phosphonium hexafluorophosphate is 0.8%.

[0160] (3) Precursor solution II is dropped onto a substrate, and 150 μL of chlorobenzene is added as an anti-solvent under spin coating conditions of 3000-5000 revolutions for 30-60 seconds to form a thin wet film on the surface of the substrate. The substrate is a hole transport layer (PEDOT:PSS layer) formed by a PEDOT:PSS solution.

[0161] (4) The substrate and the thin wet film on the surface thereof are annealed at 80° C. for 10 min to obtain a stacked PEDOT:PSS layer and a tin-based perovskite film.

[0162] A perovskite solar cell is prepared using the tin-based perovskite film prepared as above, comprising a conductive substrate (a glass plate deposited with ITO, ITO used as an anode), a hole transport layer (PEDOT:PSS), a perovskite light absorbing layer (tin-based perovskite film), an electron transport layer (including a C60 layer and a BCP interface modification layer), and a cathode (metal electrode Ag) which are stacked in sequence.

[0163] The perovskite light-absorbing layer of the perovskite solar cell of this embodiment uses the same amount of brominated tris(dimethylamino)phosphonium hexafluorophosphate to replace the 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate in Example 1. The preparation process of the perovskite solar cell includes:

[0164] S1, treating a glass substrate deposited with ITO (referred to as ITO glass substrate), performing continuous multi-step ultrasonic cleaning on the glass substrate deposited with ITO, adding a detergent, deionized water, acetone, and ethanol in each ultrasonic cleaning tank in turn; drying the glass substrate deposited with ITO after ultrasonic cleaning; irradiating the cleaned glass substrate deposited with ITO with ultraviolet light, wherein the transmittance of the ITO glass substrate is 90%, the impedance is 7 ohms, and the model is 1.1mm 7 ohms; the cleaning agent is a glass cleaning agent purchased from Guangzhou Daily Chemical, and the specification is 12basic.

[0165] S2, preparation of PEDOT:PSS hole transport layer, the PEDOT:PSS solution was filtered, coated on a glass substrate deposited with ITO under spin coating conditions of 5000r / 30s, and then annealed on a hot plate at 140°C for 15min to obtain a PEDOT:PSS hole transport layer (thickness 50nm).

[0166] S3, preparation of perovskite light absorbing layer (tin-based perovskite film): using the PEDOT:PSS hole transport layer as the substrate, a tin-based perovskite film with a thickness of 0.3 μm is prepared on the surface of the PEDOT:PSS hole transport layer. The specific preparation steps are the same as steps (1)-(4) in this embodiment.

[0167] S4, preparation of electron transport layer: on the surface of perovskite light absorbing layer, in a vacuum degree <10 -5 The fullerene layer and the BCP interface modification layer were sequentially deposited by thermal evaporation under the condition of 40 nm and 8 nm in thickness, respectively.

[0168] S5, preparation of metal electrode: on the surface of BCP interface modification layer, under vacuum degree <10 -5 Ag was deposited by thermal evaporation under Pa conditions with a thickness of 100 nm.

[0169] Example 8

[0170] A tin-based perovskite film, same as Example 7.

[0171] A perovskite solar cell, which differs from Example 7 only in that: in the cathode of the battery of this embodiment, Cu is used to replace the Ag in Example 7.

[0172] The perovskite solar cell comprises a conductive substrate (a glass plate deposited with ITO, ITO is used as an anode), a hole transport layer (PEDOT:PSS), a perovskite light absorption layer (tin-based perovskite film), an electron transport layer (including a C60 layer and a BCP interface modification layer), and a cathode (metal electrode Cu) which are stacked in sequence. The preparation process comprises the following steps:

[0173] S1, treating a glass substrate deposited with ITO (referred to as ITO glass substrate), performing continuous multi-step ultrasonic cleaning on the glass substrate deposited with ITO, adding a detergent, deionized water, acetone, and ethanol in each ultrasonic cleaning tank in turn; drying the glass substrate deposited with ITO after ultrasonic cleaning; irradiating the cleaned glass substrate deposited with ITO with ultraviolet light, wherein the transmittance of the ITO glass substrate is 90%, the impedance is 7 ohms, and the model is 1.1mm 7 ohms; the cleaning agent is a glass cleaning agent purchased from Guangzhou Daily Chemical, and the specification is 12basic.

[0174] S2, preparation of PEDOT:PSS hole transport layer: the PEDOT:PSS solution was filtered and coated on a glass substrate deposited with ITO under spin coating conditions of 5000r / 30s, and then annealed on a hot plate at 140°C for 15min to obtain a PEDOT:PSS hole transport layer (thickness 50nm).

[0175] S3, preparation of perovskite light absorbing layer (tin-based perovskite film): using PEDOT:PSS hole transport layer as substrate, a tin-based perovskite film with a thickness of 0.3 μm is prepared on the surface of the PEDOT:PSS hole transport layer. The specific preparation steps are the same as steps (1)-(4) in Example 7.

[0176] S4, preparation of electron transport layer: on the surface of perovskite light absorbing layer, in a vacuum degree <10 -5 The fullerene layer and the BCP interface modification layer were sequentially deposited by thermal evaporation under the condition of 40 nm and 8 nm in thickness, respectively.

[0177] S5, preparation of metal electrode: Cu was deposited on the surface of the BCP interface modification layer by thermal evaporation under vacuum conditions of <10-5Pa with a thickness of 100nm.

[0178] In order to further illustrate the technical effect of the present invention, the present invention also sets a comparative example, which is as follows:

[0179] Comparative Example 1

[0180] A tin-based perovskite film, which differs from Example 1 only in that 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate is not added to the precursor solution I in this comparative example, that is, in this comparative example, the precursor solution I is dropped onto the surface of the substrate to form a tin-based perovskite film.

[0181] The preparation process of the above-mentioned tin-based perovskite film includes the following steps:

[0182] (1) Formamidinium iodide (FAI), stannous iodide (SnI2) and stannous fluoride (SnF2) were weighed in a glove box at a molar ratio of 1:1:0.1 and dissolved in a DMF / DMSO (DMF / DMSO volume ratio is 4:1) mixed solution to obtain a 1 mol / L concentration of FASnI3 perovskite precursor solution (referred to as precursor solution I).

[0183] (2) Precursor solution I is dropped onto a substrate, and 150 μL of chlorobenzene is added as an anti-solvent at 3000-5000 rpm for 30-60 seconds to form a thin wet film on the substrate surface. The substrate is a hole transport layer (PEDOT:PSS layer) formed by a PEDOT:PSS solution.

[0184] (3) The substrate and the thin wet film on the surface thereof are annealed at 80° C. for 10 min to obtain a stacked PEDOT:PSS layer and a tin-based perovskite film.

[0185] A perovskite solar cell is prepared using the tin-based perovskite film prepared as above, comprising a conductive substrate (a glass plate deposited with ITO, ITO used as an anode), a hole transport layer (PEDOT:PSS), a perovskite light absorbing layer (tin-based perovskite film), an electron transport layer (including a C60 layer and a BCP interface modification layer), and a cathode (metal electrode Ag) which are stacked in sequence.

[0186] A perovskite solar cell, which differs from Example 1 only in that: in the preparation process of the perovskite light-absorbing layer of the cell described in this comparative example, 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate is not added to the precursor solution I, that is, in this comparative example, the precursor solution I is dropped onto the surface of the hole transport layer (PEDOT:PSS) to form a tin-based perovskite film with a thickness of 0.3 μm to obtain the perovskite light-absorbing layer. The preparation process of the above perovskite solar cell includes:

[0187] S1, treating a glass substrate deposited with ITO (referred to as ITO glass substrate), performing continuous multi-step ultrasonic cleaning on the glass substrate deposited with ITO, adding a detergent, deionized water, acetone, and ethanol in each ultrasonic cleaning tank in turn; drying the glass substrate deposited with ITO after ultrasonic cleaning; irradiating the cleaned glass substrate deposited with ITO with ultraviolet light, wherein the transmittance of the ITO glass substrate is 90%, the impedance is 7 ohms, and the model is 1.1mm 7 ohms; the cleaning agent is a glass cleaning agent purchased from Guangzhou Daily Chemical, and the specification is 12basic.

[0188] S2, preparation of PEDOT:PSS hole transport layer, the PEDOT:PSS solution was filtered, coated on a glass substrate deposited with ITO under spin coating conditions of 5000r / 30s, and then annealed on a hot plate at 140°C for 15min to obtain a PEDOT:PSS hole transport layer (thickness 50nm).

[0189] S3, preparation of perovskite light absorbing layer (tin-based perovskite film): using PEDOT:PSS hole transport layer as substrate, a tin-based perovskite film with a thickness of 0.3 μm is prepared on the surface of the PEDOT:PSS hole transport layer. The specific preparation steps are the same as steps (1)-(3) in this comparative example.

[0190] S4, preparation of electron transport layer: on the surface of perovskite light absorbing layer, in a vacuum degree <10 -5 The fullerene layer and the BCP interface modification layer were sequentially deposited by thermal evaporation under the condition of 40 nm and 8 nm in thickness, respectively.

[0191] S5, preparation of metal electrode: on the surface of BCP interface modification layer, under vacuum degree <10 -5 Ag was deposited by thermal evaporation under Pa conditions with a thickness of 100 nm.

[0192] Test example

[0193] The performance tests of the tin-based perovskite thin films and perovskite solar cells obtained in the above-mentioned Examples 1 to 8 and Comparative Example 1 of the present invention were carried out, specifically including:

[0194] (1) Microscopic testing was performed on the tin-based perovskite films obtained in Example 1 and Comparative Example 1, specifically including: Scanning electron microscope images of the tin-based perovskite films of Comparative Example 1 and Example 1 were as follows: Figure 3-4 The grain size distribution diagrams of the tin-based perovskite film of Comparative Example 1 and Example 1 are as follows: Figure 5-6 .

[0195] Depend on Figure 3 to Figure 6It can be seen that the tin-based perovskite film prepared by the present invention contains grains with a particle size of 0.1 to 1 μm, and the grains are relatively uniform, the film has a small roughness and a relatively high flatness.

[0196] (2) Photovoltaic performance test of perovskite solar energy, specifically including the following steps:

[0197] The current density-voltage (JV) characteristic curve of the battery was tested under a simulated light source of 100 mW / cm2 of AM1.5G (Enlitech Solar Simulator SS-F5-3A); the measurement was carried out by a computer-controlled Keithley 2400 source measurement unit in a nitrogen-filled glove box without encapsulation; the external quantum efficiency (EQE) was measured by a DSR100UV-B spectrometer with an SR830 lock-in amplifier at room temperature, air (40% humidity), without encapsulation, and the light source was a bromine tungsten lamp.

[0198] The test results of the current density-voltage characteristic curves of the perovskite solar cells provided in Examples 1, 3, 5, 7 and Comparative Example 1 are shown in Table 1 below.

[0199] Table 1 Current density-voltage characteristics of perovskite solar cells of the present invention

[0200]

[0201]

[0202] As shown in Table 1, compared with other embodiments, the tin-based perovskite solar cell using 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate additive to assist film formation has the best photoelectric performance, with an open circuit voltage of 0.86 V and a current of 23.19 mA / cm 2 The short-circuit current density, fill factor of 75.20% and photoelectric conversion efficiency of 15.00% are significantly improved compared with the device efficiency prepared by the film formation method without additive assistance in Comparative Example 1.

[0203] In traditional tin-based perovskite materials, Sn 2+ Easy oxidation can cause instability in tin-based perovskite devices and seriously affect the photoelectric conversion efficiency of the devices.

[0204] The tin-based perovskite film provided by the present invention is formed on a substrate by a mixed solution containing 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate and a perovskite precursor solution, to obtain a tin-based perovskite film bonded to the surface of the substrate. Under the synergistic effect of 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate and the perovskite precursor solution, the defects of the tin-based perovskite film can be improved. Compared with the existing tin-based perovskite film, the defects of MA or FA vacancy defects, Sn 2+ The defects caused by oxidation, the anti-site defects of Sn-I, if the tin-based perovskite film can be used to prepare electronic devices, can improve the stability of electronic devices. Therefore, the tin-based perovskite film of the present invention has the prospect of being applied to other optoelectronic information functional materials, such as photodetectors, LED light-emitting devices and field effect transistors. In addition, in the process of film formation of the mixed solution of the perovskite precursor solution, 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate is used as a perovskite precursor solution additive to inhibit the Sn in the tin-based perovskite. 2+ The oxidation of tin-based perovskite films can be improved, and the crystal quality of tin-based perovskite films can be improved, thereby solving the problem of difficult film formation and low efficiency of tin-based perovskite films. Specifically, 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate has a reducing property and can react with Sn of tin-based perovskite. 2+ interaction, which can effectively inhibit the Sn 2+ The present invention can regulate the crystallization kinetics of the growth of tin-based perovskite films, improve the defects of difficult film formation, low efficiency and poor stability of tin-based perovskite films, and thus improve the stability and photoelectric performance of perovskite films. The present invention solves the problem that the stability of existing tin-based perovskite films is poor, and the traditional method for preparing tin-based perovskite films lacks effective control over the process of tin-based perovskite film formation, resulting in many defects in the prepared tin-based perovskite films.

[0205] In the present invention, 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate is used as an additive to assist the growth of high-quality tin-based perovskite films in perovskite solar cells, which can improve the photoelectric performance and service life of solar cells. In addition, according to a reasonable battery device structure, a conductive substrate, a hole transport layer, an electron transport layer and a metal electrode are matched to form a complete solar cell device. The resulting solar cell can have good stability while achieving a photoelectric conversion efficiency of more than 14%, which can provide a technical basis for future commercial development.

[0206] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A tin-based perovskite material, characterized in that: The composition is composed of hexafluorophosphate and tin source in a molar ratio of 0.1 to 1.5:

100.

2. The tin-based perovskite material according to claim 1, characterized in that: The tin source is a perovskite precursor solution or stannous halide.

3. The tin-based perovskite material according to claim 2, characterized in that: The chemical formula of the perovskite precursor is AB1Y1Y2Y3 or AB1B2Y1Y2Y3, wherein A is a formamidinium cation or a methylamine cation, B1 is a tin ion, B2 is a lead ion, and Y1, Y2, and Y3 are each independently a halogen ion.

4. The tin-based perovskite material according to claim 1, characterized in that: The hexafluorophosphate is at least one of 2-(trifluoromethyl)-1,3-bis(dimethylamino)trimethylene hexafluorophosphate, tetramethylchloroformamidine hexafluorophosphate, benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate or bromotris(dimethylamino)phosphonium hexafluorophosphate.

5. A tin-based perovskite film, characterized in that: Prepared from the tin-based perovskite material according to any one of claims 1 to 4.

6. A method for preparing a tin-based perovskite film according to claim 5, characterized in that: The following steps are involved: A tin source and hexafluorophosphate are mixed at a molar ratio of 100:0.1-1.5 to obtain a mixture, the mixture is spin-coated on a substrate surface, and an anti-solvent is added to obtain a wet film; the wet film is annealed at 50-250° C. to obtain a tin-based perovskite film.

7. The preparation method according to claim 6, characterized in that: The annealing treatment time is 5 to 90 minutes.

8. The preparation method according to claim 6, characterized in that: The tin-based perovskite film has a thickness of 0.05 to 10 μm and a roughness of less than 50 nm.

9. Use of the tin-based perovskite film according to claim 5 in preparing perovskite solar cells.

Citation Information

Patent Citations

  • Tin-lead perovskite thin film and tin-lead perovskite solar cell

    CN116761478A

  • Perovskite solar cell with excellent reverse bias stability and preparation method thereof

    CN118434165A

Cited By

  • Preparation method of tin-based perovskite thin film

    CN122054896A